Pelaksanaan dan Evaluasi Kegiatan Pelatihan Penguatan Storytelling Produk Desa Wisata Dukuh Penaban, Kabupaten Karangasem - Dianasari, Dewa Ayu Made Lily; Suasapha, Anom Hery; Lilasari, Luh Nyoman Tri; Sukariyanto, I Gede Made; Aridayanti, Dewa Ayu Nyoman (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This article discusses the implementation of Community Service (PKM) activities conducted by lecturers of the Tourism Destination Study Program (DEP) at Bali Tourism Polytechnic in Dukuh Penaban Tourism Village. The PKM activity, which focused on